Challenges in 21st Century of Teaching Critical Thinking: Navigating Creativity Challenges in Elementary Schools - Muzaki, Ferril Irham; Dawud (Widyantara, 2024)
This exploration explores the vital part of critical thinking in abecedarian education within the frame of 21st century literacy. In the fleetly evolving educational geography, fostering critical thinking chops in abecedarian academy is imperative for preparing scholars to thrive in a complex and dynamic world. The abstract highlights crucial rudiments of 21st century literacy, emphasizing the integration of critical thinking into the class. Keywords similar as abecedarian education, critical thinking, 21st century literacy, cognitive development, problem-working, and rigidity emphasize the interconnectedness of these generalities. The abstract underscores the significance of nurturing logical chops from an early age to equip scholars with the cognitive tools necessary for success in the contemporary educational terrain and beyond. The community between critical thinking and creativity is a potent force that propels individualities, educational institutions, and societies toward intellectual vitality and innovative excellence. Feting and fostering this interplay aren’t just an educational imperative but a societal necessity. By cultivating both critical thinking and creativity, we empower individualities to navigate the complications of the ultramodern world with intellectual perceptivity, innovative faculty, and a commitment to progress.   Tantangan Berpikir Kritis di Abad ke-21: Analisis Kompleksitas Menumbuhkan Kreativitas di Sekolah Dasar Penjelajahan ini mengeksplorasi peran penting berpikir kritis dalam pendidikan abjad dalam kerangka literasi abad ke-21. Dalam lanskap pendidikan yang berkembang pesat, pengembangan keterampilan berpikir kritis di sekolah dasar menjadi penting untuk mempersiapkan siswa agar dapat berkembang di dunia yang kompleks dan dinamis. Abstrak ini menyoroti unsur-unsur penting literasi abad ke-21, dengan menekankan integrasi berpikir kritis dalam kurikulum. Kata kunci seperti pendidikan abjad, berpikir kritis, literasi abad ke-21, perkembangan kognitif, pemecahan masalah, dan ketangguhan menekankan keterkaitan konsep-konsep tersebut. Abstrak ini menegaskan pentingnya membina kemampuan berpikir logis sejak dini untuk membekali siswa dengan alat-alat kognitif yang diperlukan untuk sukses dalam lingkungan pendidikan kontemporer dan di masa depan. Hubungan antara berpikir kritis dan kreativitas adalah kekuatan yang mendorong individu, lembaga pendidikan, dan masyarakat menuju keberlanjutan intelektual dan keunggulan inovatif. Memperingati dan memajukan interaksi ini bukan hanya suatu keharusan pendidikan tetapi juga suatu keharusan sosial. Dengan membudayakan berpikir kritis dan kreativitas, kita memberdayakan individu untuk menavigasi kompleksitas dunia modern dengan kecerdasan intelektual, kemampuan inovatif, dan komitmen untuk kemajuan.